Job Satisfaction of Selected Rural Community School Teachers in Nepal (Surkhet Journal, 2025)
The purpose of the study entitled Job Satisfaction of Selected Rural Community School Teachers in Nepal was to explore the factors that impact on job satisfaction of rural community school teachers in Nepal. The study employed a phenomenological research design and a qualitative method within the interpretive paradigm. Four public secondary schools were selected through purposive sampling, along with four head teachers, two permanent teachers, three government-subsidized contract teachers, and two teachers recruited from internal sources. Data were collected through semi-structured, in-depth interviews. The study shows that the existing pay scale, school environment, distribution of opportunities, and the relationship between teachers and parents were the main factors of teachers' job satisfaction. Internal sources teachers' pay scale was based on nominal only. There was no team spirit, teamwork, co-ordination, cooperation, ideas sharing, or warm discussion about their professional careers between teachers. Backbiting, cheating, and political biasness were highly placed in school by which an internal environment was not peaceful in schools. Delegation of authority, promotion policy, transfer system, and teachers’ selection for training were not fair in the school. Localization, political ideology, kinship was highly placed in the distribution of opportunities.